PENGARUH MODEL PEMBELAJARAN DAN MOTIVASI BERPRESTASI TERHADAP KETERAMPILAN SOSIAL PADA MATA PELAJARAN IPS - Ruslan Hadiwijaya; Endah Andayani; Endang Surjati (Jurnal Penelitian dan Pendidikan IPS, 2024)
This research aims to: (1) analyze the influence of direct learning models, problem-based learning, and achievement motivation on students' social skills in social studies subjects, (2) analyze the influence of direct learning models on students' social skills, (3) analyze the influence of the problem-based learning model on students' social skills, and (4) analyzing the influence of achievement motivation on students' social skills. This research is quantitative. The sample used 25% of 315 class VIII students at SMP Negeri 1 Pamekasan totaling 80 students. The research results show that: first, there is a significant influence between the direct learning model, problem-based learning, and achievement motivation on students' social skills. Based on the analysis of significance values, the sig value = 0.000, so the significance value is <0.05. Second, there is no significant effect of the direct learning model on students' social skills. Based on the analysis of significance values, the sig value = 0.929, so the significance value is > 0.05. Third, there is a significant influence between problem-based learning on students' social skills. Based on the analysis of significance values, the sig value = 0.004, so the significance value is <0.05. Fourth, there is a significant influence of achievement motivation on students' social skills. Based on the analysis of significance values, the sig value = 0.000, so the significance value is <0.05. The results of this research can be concluded that there is a significant influence between the direct learning model, problem-based learning, and achievement motivation on students' social skills